DUTCH COLONIAL ARCHITECTURE AND CITY DEVELOPMENT OF MAKASSAR (DIMENSI: Journal of Architecture and Built Environment, 2004)
Indonesian old cities as the sites of government, trading, and ports have been established before the arrival of the Europeans. The form and pattern of settlements which served as the centres of the hinterlands were influenced by Indian or Hindu and afterwards by Chinese and European cultures. Makassar has been the dominant trading centre in Nusantara Archipelago. Its strategic location on South West peninsula of the sprawling island of Sulawesi gave it excellent access to the busy sea lanes of Java Sea, the Makassar straits, the Celebes and Banda seas and hence to many local trading networks as well as to the crucial long distance trade with India, China, and ultimately with Europe. The history of the city of Makassar began with the fort which was turned into the site of government, military and trade after the destruction of the Somba Opu fort. Despite of its similarities, there were principal differences with cities in Java which were also established in the same period.